The impact of idiosyncratic risk of banking sector on oil, stock market, and fiscal indicators of Sultanate of Oman. (17th January 2018) - Al Shubiri, Faris Nasif; Jamil, Syed Ahsan
Idiosyncratic risk (IDR) is defined in general as the uncertainties of return to investors from an investment portfolio leading to diversification or hedging to mitigate and avoid such risks. This article aims to analyze the IDR of banking sector on oil (OI), stock market indicator (SMI), and fiscal indicator (FI) of Sultanate of Oman. This article examines the IDR of six banking sectors listed in Muscat Security Market (MSM), from 2009 to 2015. Financial modeling is used to determine the IDR of banking sector treated as an independent variable. This study uses three main critical dependent variables, OI, SMI, and FI. The ordinary least squares regression results depicted that there is a statistically significant impact on all of SMIs in MSM 30 share price and its market capitalization with direction of oil exports as OI being significant, as well as total expenditure as percentage of gross domestic product is significant as FI at different significant levels 1%, 5%, and 10%. The findings of the research indicated a weak investor's protection mechanism and strongly recommend heightened government focus on stressing the importance of having a formal system based on stability, safety, transparency, and supervision of the implementation of contracts so as to protect small investors, eventually leading to increased investments in stocks. Facilitation and encouragement to foreign direct investment will also lead to increase in the performance of fiscal management indicators and improve the export prices of oil, giving a boost to the economic and financial system of the nation.